(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The article analyzes promising directions for the development of regulation and supervision by the Central Bank of the Republic of Uzbekistan over the activities of commercial banks and credit institutions. The prospects for regulation of commercial banks by the Central Bank (CB) are associated with enhanced supervision and digitalization, which will help ensure financial stability, protect the rights of consumers and investors, and improve the accessibility of financial services.